Subunit Vaccines Using TLR Triagonist Combination Adjuvants Provide Protection Against Coxiella burnetii While Minimizing Reactogenic Responses - Fratzke, Alycia P.; Jan, Sharon; Felgner, Jiin; Liang, Li; Nakajima, Rie; Jasinskas, Algis; Manna, Saikat; Nihesh, Fnu N.; Maiti, Sampa; Albin, Tyler J.; Esser-Kahn, Aaron P.; Davies, D. Huw; et al. (Frontiers in Immunology, 2021)
Q fever is caused by the obligate intracellular bacterium, Coxiella burnetii, a designated potential agent of bioterrorism because of its route of transmission, resistance to disinfectants, and low infectious dose. The only vaccine licensed for human use is Q-VAX® (Seqirus, licensed in Australia), a formalin-inactivated whole-cell vaccine, which produces severe local and systemic reactogenic responses in previously sensitized individuals. Accordingly, the U.S. Food and Drug Administration and other regulatory bodies around the world, have been reluctant to approve Q-VAX for widespread use. To obviate these adverse reactions, we prepared recombinant protein subunit vaccine candidates containing purified CBU1910, CBU0307, CBU0545, CBU0612, CBU0891, and CBU1398 proteins and TLR triagonist adjuvants. TLR triagonist adjuvants combine different TLR agonists to enhance immune responses to vaccine antigens. We tested both the protective efficacy and reactogenicity of our vaccine candidates in Hartley guinea pigs using intratracheal infection with live C. burnetii. While all of our candidates showed varying degrees of protection during challenge, local reactogenic responses were significantly reduced for one of our vaccine candidates when compared with a formalin-inactivated whole-cell vaccine. Our findings show that subunit vaccines combined with novel TLR triagonist adjuvants can generate protective immunity to C. burnetii infection while reducing reactogenic responses.